KERAGAMAN DAN TITIK IMPAS USAHA TANI ANEKA SAYURAN PADA LAHAN SAWAH DI KABUPATEN KARAWANG, JAWA BARAT - DARWIS, VALERIANA; MUSLIM, CHAIRUL (Universitas Sebelas Maret, 2013)
Vegetables are a strategic crop in the agricultural sector and one vegetable production centers in Indonesia is the regency Karawang province of West Java. Vegetable crops can be grown in lowland, medium and high. The purpose of this paper was to determine variability and analysis of vegetable farming in paddy fields as well as the reasons why farmers want to grow vegetables instead of rice fields.